2021
DOI: 10.1186/s12891-021-03957-8
|View full text |Cite
|
Sign up to set email alerts
|

A radiostereometric and clinical long-term follow-up study of the surface replacement trapeziometacarpal joint prosthesis

Abstract: Background The aim of this study was to determine long-term survival and clinical outcomes of the surface replacement trapeziometacarpal joint prosthesis (SR™TMC) and to evaluate implant migration using radiostereometric analysis (RSA). Methods In this clinical long-term follow-up study outcomes of ten patients who received the SR™TMC joint prosthesis were evaluated using DASH and Nelson scores, Visual Analogue Scale (VAS) of pain, and key pinch st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…This is in line with previous RSA studies assessing migration of small trapeziometacarpal joint implants. 19,20,36 A third limitation was the absence of repeat examinations. These are needed to determine the clinical precision of the migration calculations, as recommended in the guidelines for standardization of RSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with previous RSA studies assessing migration of small trapeziometacarpal joint implants. 19,20,36 A third limitation was the absence of repeat examinations. These are needed to determine the clinical precision of the migration calculations, as recommended in the guidelines for standardization of RSA.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these difficulties, studies on trapeziometacarpal joint replacements showed high accuracy in measuring translations but low accuracy for rotations. 19,45 RSA analysis for the MTP-1 joint prosthesis in the forefoot has never been published, and thus migrations were neither quantified nor linked to clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%